A preliminary study on one folio of Tibetan tantric ritual text recently collected by the national library of China. Issue 2 (3rd July 2021) - Saerji,
ABSTRACT: This article focuses on one folio of Tibetan tantric ritual text recently collected by the National Library of China, based on a tentative translation, discussing its peculiarities on Tibetan orthography and expression, its esoteric elements, especially its rituals of the dead and making clay tablet ( tsha tsha ), attempts to trace the Indian origin of the text and its influences on related Tibetan texts.